Adiabatic Connection for Range‐Separated Hybrid Functionals. Issue 4 (12th February 2022) - Garrick, Rachel; Kronik, Leeor; Gould, Tim
Abstract: A generalized adiabatic connection that applies to any type of range‐separated hybrid (RSH) functional employed within generalized Kohn–Sham (KS) theory is presented. This generalized relation is then used to derive a definition for a rigorous distinction between multiplicative exchange and correlation components. The developed adiabatic connection is defined in terms of both generalized and conventional KS orbitals. It is shown, however, that using only the KS orbitals produces an error that is O ( ε 2 ) O(ε ^2), where ε ε is fully defined in terms of parameters in the RSH functional, and is found to be small in practical calculations. It is expected that this new adiabatic connection can assist in the development of new RSH functionals and the assessment of existing ones. Abstract : The adiabatic connection formula bridges any interacting many‐electron system and its noninteracting Kohn–Sham system by gradually "turning on/off" the electron–electron interaction, which makes it very useful for density functional development and analysis. Here, a generalized adiabatic connection, which applies to any range‐separated hybrid (RSH) functional employed within generalized Kohn–Sham theory, is presented, and its consequences are discussed.